Altered leptin signaling and attenuated cardiac vagal activity in rats with type 2 diabetes - Evans, Anthony J.; Tu, Huiyin; Li, Yu; Shabaltiy, Boris; Whitney, Lauren; Carpenter, Kassidy; Li, Yu-long (Frontiers in Physiology, 2025)
IntroductionThe leading cause of death in type 2 diabetes mellitus (T2DM) patients is cardiovascular-related events, including myocardial infraction-induced ventricular arrhythmia. Previous studies have shown that T2DM-induced functional remodeling of cardiac vagal postganglionic (CVP) neurons contributes to ventricular arrhythmogenesis. As leptin resistance is common in T2DM patients, and CVP neurons are located in epicardial adipose pads, a tissue that secretes leptin, in this study we aimed to elucidate a correlation between leptin resistance and CVP neuronal dysfunction in T2DM.MethodsA high fat-diet/low dose streptozotocin-induced T2DM rat model was used in this study to characterize T2DM-induced alterations in cardiac parasympathetic tone, determined by changes in baroreflex sensitivity and CVP neuronal excitability. The impact of leptin resistance on CVP neurons was also studied by examining the expression of leptin in epicardial adipose pads, and leptin receptors and uncoupling protein 2 (UCP2) in CVP neurons.ResultsT2DM rats exhibited diminished baroreflex sensitivity, and decreased CVP neuronal excitability, demonstrated by a reduced frequency of action potentials, diminished nAChR currents, and an attenuated response to nicotine stimulation. Additionally, compared to sham animals, the expression of leptin receptors and UCP2 in CVP neurons was reduced as early as 4 weeks post-T2DM although the leptin levels in epicardial adipose pads was increased during the progression of T2DM, which demonstrated the occurrence of leptin resistance in T2DM CVP neurons.ConclusionCardiac parasympathetic dysfunction in T2DM rats is due, in part, to functional remodeling of CVP neurons. As leptin resistance develops as early as 4 weeks post-T2DM induction, diminished leptin receptors-UCP2 signaling may contribute to CVP neuronal dysregulation.